Aramaic and Figural Stamp Impressions on Bricks of the Sixth Century B.C. from Babylon - Sass, Benjamin (2010)
With Drawings by Noga Z’evi; = Ausgrabungen der Deutschen Orient-Gesellschaft in Babylon 10.